2019
DOI: 10.3390/cancers11121827
|View full text |Cite
|
Sign up to set email alerts
|

FLT3-ITD Activates RSK1 to Enhance Proliferation and Survival of AML Cells by Activating mTORC1 and eIF4B Cooperatively with PIM or PI3K and by Inhibiting Bad and BIM

Abstract: FLT3-ITD is the most frequent tyrosine kinase mutation in acute myeloid leukemia (AML) associated with poor prognosis. We previously found that FLT3-ITD activates the mTORC1/S6K/4EBP1 pathway cooperatively through the STAT5/PIM and PI3K/AKT pathways to promote proliferation and survival by enhancing the eIF4F complex formation required for cap-dependent translation. Here, we show that, in contrast to BCR/ABL causing Ph-positive leukemias, FLT3-ITD distinctively activates the serine/threonine kinases RSK1/2 thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 66 publications
0
33
0
Order By: Relevance
“…However, CXCR4 inhibition by LY2501924 induced de-phosphorylation of ERK, even in the presence of stromal cells, which was supported by inhibition of phosphorylation of the ribosomal protein S6 (rpS6). rpS6 is known to be directly phosphorylated through activation of p90 ribosomal S6 kinase by MAPK pathway in FLT3-ITD-AML [ 22 ] as well as activation of p70-S6 kinase 1 by PI3K/AKT/mTOR pathway. Thus, the anti-apoptotic effects of BM stroma appear to correlate with the persistent activation of ERK, which could be effectively reversed by disruption of the CXCL12/CXCR4 axis by LY2510924.…”
Section: Resultsmentioning
confidence: 99%
“…However, CXCR4 inhibition by LY2501924 induced de-phosphorylation of ERK, even in the presence of stromal cells, which was supported by inhibition of phosphorylation of the ribosomal protein S6 (rpS6). rpS6 is known to be directly phosphorylated through activation of p90 ribosomal S6 kinase by MAPK pathway in FLT3-ITD-AML [ 22 ] as well as activation of p70-S6 kinase 1 by PI3K/AKT/mTOR pathway. Thus, the anti-apoptotic effects of BM stroma appear to correlate with the persistent activation of ERK, which could be effectively reversed by disruption of the CXCL12/CXCR4 axis by LY2510924.…”
Section: Resultsmentioning
confidence: 99%
“…Signaling initiated through FLT3 is one of the most important causes of the dysregulation of PI3K-Akt-mTOR signaling in AML, and FLT3 gene mutations lead to abnormal activation of the pathway [87,88]. Mutations in the FLT3 gene are among the most frequent mutations seen in AML [89].…”
Section: Pi3k-akt-mtor Signaling In Amlmentioning
confidence: 99%
“…For instance, it has been reported that PIM-1 elevates RTKs upon inhibition of Akt, leading to drug resistance [155,156]. Upregulation of PIM-1 mediated by FLT3-ITD enhanced survival through protection of the mTOR/4E-BP1/myeloid cell leukemia 1 (Mcl-1) pathway, which was abrogated by inhibition of the STAT5/PIM kinase axis [157][158][159][160][161].…”
Section: Crosstalk Of the Pi3k/akt/mtor Signaling Pathway With Other mentioning
confidence: 99%